2019
DOI: 10.1523/jneurosci.3248-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Learning Efficacy with Noninvasive Brain Stimulation in Intact and Brain-Damaged Humans

Abstract: Numerous behavioral studies have shown that visual function can improve with training, although perceptual refinements generally require weeks to months of training to attain. This, along with questions about long-term retention of learning, limits practical and clinical applications of many such paradigms. Here, we show for the first time in female and male human participants that just 10 d of visual training coupled with transcranial random noise stimulation (tRNS) over visual areas causes dramatic improveme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 87 publications
5
59
0
Order By: Relevance
“…Moreover, van der Groen & Wenderoth utilized stimulus-locked short bursts of online tRNS 427 (2.04s at a time), whereas most tRNS studies utilize longer blocks of stimulation (> 10 min), similar 428 to what was employed here -e.g. (Herpich et al, 2019, Fertonani et al, 2011, Pirulli et al, 2013. 429 This is relevant, as it was demonstrated by Chaieb et al (2011) that tRNS stimulation lasting 5 430 minutes (or longer) increases cortical excitability in motor cortex (assessed by TMS-induced MEPs), 431 suggesting that van der Groen & Wenderoth's effect may rely on a short-term, induced white noise signal rather than a change in excitability.…”
Section: Trns Mimics the Beneficial Effects Of Endogenous Attentionalmentioning
confidence: 98%
“…Moreover, van der Groen & Wenderoth utilized stimulus-locked short bursts of online tRNS 427 (2.04s at a time), whereas most tRNS studies utilize longer blocks of stimulation (> 10 min), similar 428 to what was employed here -e.g. (Herpich et al, 2019, Fertonani et al, 2011, Pirulli et al, 2013. 429 This is relevant, as it was demonstrated by Chaieb et al (2011) that tRNS stimulation lasting 5 430 minutes (or longer) increases cortical excitability in motor cortex (assessed by TMS-induced MEPs), 431 suggesting that van der Groen & Wenderoth's effect may rely on a short-term, induced white noise signal rather than a change in excitability.…”
Section: Trns Mimics the Beneficial Effects Of Endogenous Attentionalmentioning
confidence: 98%
“…As the field of stroke rehabilitation advances, efforts towards clinical implementation will be aided by development of additional metrics and biomarkers to further stratify patients' recovery potential (59). Moreover, while the present study employed a CDDI training program because it was previously identified as highly effective in chronic CBs (7,9,10), we have yet to determine which training stimulus and paradigm is best suited to treat subacute CBs -ongoing work is investigating this question, as well as the use of adjuvants such as non-invasive brain stimulation, which may further augment the effects of training (60). Clinical translation will ultimately depend on all these determinations, as well as the development of services to teach patients how to train properly (especially with accurate fixation), while automatically monitoring their progress and customizing their training locations as needed.…”
Section: Research Challenges and Future Steps Towards Clinical Implemmentioning
confidence: 99%
“…In line with this view, an increasing body of literature highlights the successful application of transcranial random noise stimulation (tRNS), a form of transcranial electrical stimulation, to modulate performance in a variety of training paradigms and cognitive tasks 5,6 . tRNS has been used to improve perception [7][8][9] , numerosity discrimination 10,11 , executive control and multitasking 12 , motor skill learning 13,14 , fluid intelligence 15 , and arithmetic learning [16][17][18] . Furthermore, tRNS has been reported in several studies to yield a stronger effect than anodal transcranial direct current stimulation 6,7,19,20 .…”
Section: Introductionmentioning
confidence: 99%